Psoas muscle index and psoas muscle density are associated with functional status in patients with degenerative lumbar spinal stenosis - Hou, Xiaofei; Hu, Hailiang; Kong, Chao; Zhang, Sitao; Wang, Wei; Lu, Shibao (Journal of back and musculoskeletal rehabilitation, 2024)
BACKGROUND: The factors affecting lumbar spinal function in patients with degenerative lumbar spinal stenosis (DLSS) are still unclear. OBJECTIVE: This study explored psoas major muscle morphology in patients with DLSS and its association with their functional status. METHODS: A retrospective study was conducted on 288 patients with DLSS and 260 control subjects. Psoas major muscle evaluation included three morphometric parameters at the L3/4 disc level: psoas major index (PMI), muscle attenuation, and psoas major morphological changes (MPM). The association between psoas major morphology and functional status was assessed using the Oswestry disability index (ODI). RESULTS: Both female and male patients with DLSS had a higher PMI and lower muscle attenuation. PMI and muscle attenuation were inversely correlated with age in the DLSS group. After multivariable analyses, the PMI and psoas major muscle attenuation were positively correlated with patients’ functional status. CONCLUSION: The PMI and muscle attenuation were positively correlated with functional status in patients with DLSS. These findings have important implications for physiotherapy programs of postoperative rehabilitation and conservative management of DLSS.